Dual Functions of Performance Improvement and Lead Leakage Mitigation of Perovskite Solar Cells Enabled by Phenylbenzimidazole Sulfonic Acid. Issue 2 (24th December 2021) - Hu, Yanqiang; He, Zhengyan; Jia, Xiangrui; Zhang, Shufang; Tang, Yanfeng; Wang, Jin; Wang, Minmin; Sun, Guangping; Yuan, Guoliang; Han, Liyuan
Abstract: With the continuous improvement of performance of lead‐based perovskite solar cells (PSCs), the potential harm of water‐soluble lead ion (Pb 2+ ) to environment and public health is emerging as a major obstacle to their commercialization. Herein, an amphoteric phenylbenzimidazole sulfonic acid (PBSA) that is almost insoluble in water is added to the perovskite precursor to simultaneously regulate crystallization growth, passivate defects, and mitigate lead leakage of high‐performance PSCs. Through systematic research, it is found that PBSA can not only regulate the crystallization of perovskite grains to form the film, but also passivate the defects of annealed films mainly due to the strong interaction between the functional groups in PBSA and Pb 2+, which greatly improves the crystallinity and stability of perovskite films. Consequently, the highest power conversion efficiency of 23.27% is achieved in 0.09 cm 2 devices and 15.31% is obtained for large‐area modules with an aperture area of 19.32 cm 2, along with negligible hysteresis and improved stability. Moreover, the leakage of lead ions from unpackaged devices is effectively prevented owing to the strong coupling between PBSA molecules and water‐soluble Pb 2+ to form insoluble complexes in water, which is of great significance to promote the application of optoelectronic devices based on lead‐based perovskite materials. Abstract : An amphoteric phenylbenzimidazole sulfonic acid is used to simultaneously regulate crystallization growth, passivate defects, and mitigate lead leakage of high‐performance perovskite solar cells. The efficiency of the optimized device is 23.27% (0.09 cm 2 ) and 15.31% (19.32 cm 2 ), respectively. Meanwhile, the leakage of lead ions from unencapsulated devices is also successfully suppressed.